Do oral combined contraceptive pills modify body image and sexual function? - Krzysztof Nowosielski (BMC, 2022)
Abstract Background The effect of hormonal contraceptives on sexual function and body image is still controversial. Existing studies have not come to definite conclusions on the association between hormonal contraceptive use and sexual function/presence of sexual dysfunction or changes in body image perception. Thus, this study aimed to evaluate the prevalence of sexual problems/dysfunction in Polish women of reproductive age (18-45 years) and to assess to what extent oral combined contraceptive pills (OCCP) impact body image, sexual function and the prevalence of female sexual dysfunction (FSD). Methods A total of 495 women were included in this cross-sectional questionnaire-based study. Sexual function was assessed by the Changes in Sexual Function Questionnaire (CSFQ), the prevalence of FSD was assessed by DSM-5 criteria, and body image was assessed by the Body Exposure during Sexual Activity Questionnaire (BESAQ). A total of 237 women using OCCP were the study group (HC), and the rest were controls (CG). A regression model was used to evaluate the influence of the selected variables on sexual function and the presence of FSD. Results The prevalence of FSD was 7.5% in HC and 2.6% in CG, and 22% compared to 14% of women in HC and CG, respectively, reported sexual problems (CSFQ). The demographic characteristics of those using other contraception methods or not using any contraception (control group) were similar. The contraceptive group was characterized by significantly higher importance of sex (4.03 vs. 3.79), worse partner's attitude toward sex (4.35 vs. 4.47), worse self-attitude toward sex (4.35 vs. 4.47), and worse body image (BESAQ) compared to controls. Among all of the variables, a lower level of anxiety (t = -1.99), positive attitudes toward sex (t = 2.05), watching erotic videos (t = 5.58) and a higher importance of sex (t = 5.66) were predictive of better sexual function (R2-0.38, F = 28.9, p = 0.0001). Conclusion Sexual behaviors and function are different in those using OCCP compared to nonusers. The prevalence of sexual problems and dysfunction was higher in those using this hormonal method of contraception; however, using OCCP was not a risk factor for either worse sexual function or sexual dysfunction. Partners' attitudes toward sex and general anxiety level were factors contributing to sexual function and the risk of sexual dysfunction in the population of women of reproductive age and should be routinely evaluated in clinical practice, especially before prescribing hormonal contraceptives.